Semi-active fuzzy control of a wind-excited tall building using multi-objective genetic algorithm - Kim, Hyun-Su; Kang, Joo-Won (Engineering structures, 2012)
► Control performance of semi-active TMD for a wind-excited tall building is evaluated. ► A 100kN MR damper is used for the semi-active TMD (STMD). ► The fuzzy logic controller is used to effectively control the STMD. ► The fuzzy logic controller is optimized by multi-objective genetic algorithms. ► Control performance of the STMD is comparable to that of active TMD in this study. In this study, a multi-objective optimal fuzzy control system for the response reduction of a wind-excited tall building has been proposed. A semi-active tuned mass damper (STMD) is used for vibration control of a 76-story benchmark building subjected to wind load. An STMD consists of a 100kN magnetorheological (MR) damper and its natural period is tuned to the first-mode natural period of vibration of the example building structure. The damping force of the MR damper is controlled by a fuzzy logic controller. A multi-objective genetic algorithm is used for optimization of the fuzzy logic controller. Both the 75th floor acceleration response of the structure and the stroke of the STMD have been used as the objective functions for this multi-objective optimization problem. Because a multi-objective optimization approach provides a set of Pareto-optimal solutions, an engineer is able to select an appropriate design for the specific performance requirement. For a comparative study, a sky–ground hook control algorithm is employed for control of the STMD. Based on numerical results, it has been shown that the proposed control system can effectively reduce the STMD motion as well as building responses compared to the comparative sky–ground hook control algorithm. In addition, the control performance of the STMD controlled by the optimal fuzzy controller is superior to that of the passive TMD and is comparable to an active TMD, but with a significant reduction in power consumption.